Mitochondrial DNA copy number as a prognostic marker is age-dependent in adult glioblastoma. Issue 1 (3rd January 2022) - Sourty, Baptiste; Dardaud, Laure-Marie; Bris, Céline; Desquiret-Dumas, Valérie; Boisselier, Blandine; Basset, Laëtitia; Figarella-Branger, Dominique; Morel, Alain; Sanson, Marc; Procaccio, Vincent; Rousseau, Audrey
Abstract: Background: Glioblastoma (GBM) is the most common and aggressive form of glioma. GBM frequently displays chromosome (chr) 7 gain, chr 10 loss and/or EGFR amplification (chr7+/chr10-/ EGFR amp). Overall survival (OS) is 15 months after treatment. In young adults, IDH1/2 mutations are associated with longer survival. In children, histone H3 mutations portend a dismal prognosis. Novel reliable prognostic markers are needed in GBM. We assessed the prognostic value of mitochondrial DNA (mtDNA) copy number in adult GBM. Methods: mtDNA copy number was assessed using real-time quantitative PCR in 232 primary GBM. Methylation of POLG and TFAM genes, involved in mtDNA replication, was assessed by bisulfite-pyrosequencing in 44 and 51 cases, respectively. Results: Median age at diagnosis was 56.6 years-old and median OS, 13.3 months. 153/232 GBM (66 %) displayed chr7+/chr10-/ EGFR amp, 23 (9.9 %) IDH1/2 mutation, 3 (1.3 %) H3 mutation and 53 (22.8 %) no key genetic alterations. GBM were divided into two groups, "Low" ( n = 116) and "High" ( n = 116), according to the median mtDNA/nuclear DNA ratio (237.7). There was no significant difference in OS between the two groups. By dividing the whole cohort according to the median age at diagnosis, OS was longer in the "High" vs "Low" subgroup (27.3 vs 15 months, P = .0203) in young adult GBM ( n = 117) and longer in the "Low" vs "High" subgroup (14.5 vs 10.2 months, P = .0116) in older adult GBM ( n = 115). POLG was highly methylated, whereas TFAM remained unmethylated. Conclusion: mtDNA copy number may be a novel prognostic biomarker in GBM, its impact depending on age.